L-type Ca2+ channel function is linked to dystrophin expression in mammalian muscle. - Friedrich, Oliver; von Wegner, Frederic; Chamberlain, Jeffrey S.; Fink, Rainer; Rohrbach, Petra (PLoS ONE, 2008)
BACKGROUND In dystrophic mdx skeletal muscle, aberrant Ca2+ homeostasis and fibre degeneration are found. The absence of dystrophin in models of Duchenne muscular dystrophy (DMD) has been connected to altered ion channel properties e.g. impaired L-type Ca2+ currents. In regenerating mdx muscle, 'revertant' fibres restore dystrophin expression. Their functionality involving DHPR-Ca2+-channels is elusive. METHODS AND RESULTS We developed a novel 'in-situ' confocal immuno-fluorescence and imaging technique that allows, for the first time, quantitative subcellular dystrophin-DHPR colocalization in individual, non-fixed, muscle fibres. Tubular DHPR signals alternated with second harmonic generation signals originating from myosin. Dystrophin-DHPR colocalization was substantial in wt fibres, but diminished in most mdx fibres. Mini-dystrophin (MinD) expressing fibres successfully restored colocalization. Interestingly, in some aged mdx fibres, colocalization was similar to wt fibres. Most mdx fibres showed very weak membrane dystrophin staining and were classified 'mdx-like'. Some mdx fibres, however, had strong 'wt-like' dystrophin signals and were identified as 'revertants'. Split mdx fibres were mostly 'mdx-like' and are not generally 'revertants'. Correlations between membrane dystrophin and DHPR colocalization suggest a restored putative link in 'revertants'. Using the two-micro-electrode-voltage clamp technique, Ca2+-current amplitudes (i(max)) showed very similar behaviours: reduced amplitudes in most aged mdx fibres (as seen exclusively in young mdx mice) and a few mdx fibres, most likely 'revertants', with amplitudes similar to wt or MinD fibres. Ca2+ current activation curves were similar in 'wt-like' and 'mdx-like' aged mdx fibres and are not the cause for the differences in current amplitudes. i(max) amplitudes were fully restored in MinD fibres. CONCLUSIONS We present evidence for a direct/indirect DHPR-dystrophin interaction present in wt, MinD and 'revertant' mdx fibres but absent in remaining mdx fibres. Our imaging technique reliably detects single isolated 'revertant' fibres that could be used for subsequent physiological experiments to study mechanisms and therapy concepts in DMD.